Labor, Labor Market and Islamic Economics: An Induction Approach - Altwijry, Othman (مجلة العلوم الإدارية و الإقتصادية, 2024)
The purpose of this study to explore moral and ethical issues regarding labor and labor market from the Islamic perspective as compared to the conventional economics. Admittedly, these matters have been found to be overlooked in both the conventional and Islamic economics’ literatures. Hence, this study presents a comparative analysis of those issues and discusses them specifically in terms of Islamic economics. The methodology employed in this study is via the inductive approach. Consequently, a major finding of this study is that Islamic labor market is entirely different from the free market due to its inimitable moral and ethical values. It also reveals that Islamic labor market considers labor not as a commodity per se but as an asset or resource that could be capitalized amicably. Furthermore, this study highlights that actually market forces do not determine wages but are in fact influenced by the skills and abilities of workers and more importantly by the moral and ethical values of the society. Unlike the conventional labor market, Islamic labor market considers the social-entrepreneurial responsibility as mutually crucial. These findings are expected to have several significant policy implications to policymakers for the benefit of consumers. Therefore, future research should duly acknowledge this fact.